Translating the Classics into the vernacular in sixteenth‐century Italy. Issue 1 (February 2015) - Merisalo, Outi
<x xml:space="preserve">Abstract</x> Whilst early‐ and mid‐fifteenth‐century Italian humanism had concentrated on ambitious new translations from Greek into Latin, rather neglecting the vernacular, the sixteenth century is characterized by a proliferation of vernacular works in all fields and, especially from the 1530s on, intense activity in translating classical works into Italian. This article discusses some material features of the original and translated publications under consideration, but especially explores linguistic choices and translation techniques used by three translators in a variety of classical texts: Antonio Brucioli (1487–1566), who translated among other things the texts discussed here, the Rhetorica ad Herennium, believed to be by Cicero (Rhetorica di Marco Tullio Cicerone, tradotta di latino in lingua thoscana, per Antonio Brucioli (Venice, 1538)), and Pliny's Naturalis historia (Historia naturale di C. Plinio Secondo. Nuovamente tradotta di latino in vulgare toscano per Antonio Brucioli (Venice, 1548)); Giovanni Andrea dell'Anguillara (1517–72), who earned lasting fame for his translation of Ovid's Metamorphoses, entitled De le Metamorfosi d'Ovidio libri III di Giovanni Andrea dell'Anguillara (Venice, 1553); and Francesco Baldelli (d. after 1587), who translated all of Caesar's histories in I commentari di C. Giulio Cesare da M. Francesco Baldelli nuouamente di lingua latina tradotti in Thoscana (Venice, 1554). These translations are considered in terms of their cultural and political context, linguistic and pragmatic characteristics, dissemination in the sixteenth century, and contribution to the ongoing development of the vernacular.